The Motivation Influence on the Performance of the Female Santri Association Management (ISPI) at the Modern Islamic Boarding School Ummul Quro Al-Islami Bogor - Sari, Indah Puspita; Shofi'unnafi, Shofi'unnafi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
The performance of the organization's management will be a replication of the organization's performance. Hence, the performance of the organization is very dependent on the performance of the management, especially for non-profit organization members who are voluntary in nature. Do they have the drive to provide maximum performance? The study aims to determine the effect of motivation on the performance of the Female Student Association Management (ISPI) at the Modern Islamic Boarding School Ummul Quro Al-Islami Bogor. The method in this study was a quantitative research method with data collection techniques through questionnaires, interviews and documentation. The data analysis technique used was descriptive analysis test, assumption test, simple linear regression test and hypothesis test using SPSS version 25 application. The results showed that motivation has a significant effect on the performance of ISPI management. It was based on the t test as evidenced by a significance value of 0.000 <0.05 which stated that Ho was rejected and Hk was accepted. The coefficient of determination test showed a value of 0.272, meaning that the presentation of the influence of motivation on performance was 27.2% while the remaining 72.8% (100%-27.2%) was influenced by other variables.